Development and Validation of the Resident Healthcare-Seeking Culture Scale (RHCS) Among Chinese Demographics in the Community Setting - Xu H; Feng J; Qiu L; Yan S; Li L; Tian Q; He Y; Lu Z (Risk Management and Healthcare Policy)
Hongbin Xu,1,* Jie Feng,1,2,* Lei Qiu,3 Shijiao Yan,3,4 Liqing Li,5 Qingfeng Tian,6 Yan He,6 Zuxun Lu1 1School of Public Health, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 2College of Public Health, Chongqing Medical University, Chongqing, People’s Republic of China; 3School of Public Health, Hainan Medical University, Haikou, Hainan, People’s Republic of China; 4Key Laboratory of Emergency and Trauma of Ministry of Education, Hainan Medical University, Haikou, Hainan, People’s Republic of China; 5Department of Management Science and Engineering, School of Economics and Management, Jiangxi Science and Technology Normal University, Nanchang, Jiangxi, People’s Republic of China; 6College of Public Health, Zhengzhou University, Zhengzhou, Henan, 450001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zuxun Lu, Department of Social Medicine and Health Management, School of Public Health, Tongji Medical College, Huazhong University of Science and Technology, No. 13 hangkong Road, Wuhan, 430030, People’s Republic of China, Tel/Fax +86 027 83693756, Email zuxunlu@yahoo.comObjective: This study aimed to develop a measurement scale with good reliability and validity to assess the reasonableness of resident healthcare-seeking culture.Methods: This investigation utilized a cross-sectional research design, employing a multi-stage random sampling technique to select adult inhabitants aged eighteen and above who possess fundamental literacy abilities. An online survey was conducted from March to April 2021 across 27 provinces in China, encompassing 911 questionnaires for scale development. This study primarily applied discriminant coefficients and exploratory factor analysis to refine the scale items. Scale reliability was assessed using Cronbach’s alpha, and split-half reliability. Scale validity was determined through content validity and structural validity. Data analysis was performed using SPSS 21.0, and structural equation modeling was executed with AMOS 23.0 software. Statistical significance was defined at P< 0.05.Results: The Resident Healthcare-seeking Culture Scale (RHCS) ultimately comprised 5 dimensions and 20 items. The cumulative explained variance of the five common factors within this scale amounts to 55.24%, satisfactorily adhering to the established criterion of social science research that the extracted factors should explain between 50% and 60% of the total variance. The Cronbach’s alpha coefficient for the total scale was 0.83. Split-half reliability was 0.87. The Pearson correlation coefficients associating the scores from the five dimensions with the overall scale score were 0.78, 0.65, 0.65, 0.64, and 0.42, respectively, all statistically significant with P-values less than 0.001. The results of confirmatory factor analysis suggested that RMR=0.045, GFI=0.952, AGFI=0.936, PGFI=0.712, NFI=0.917, IFI=0.944, TLI=0.931, CFI = 0.943, and RMSEA = 0.046.Conclusion: The measurement scale for healthcare-seeking culture among Chinese residents exhibits superior reliability and validity, serving as an effective instrument for hospital administrators to evaluate the reasonableness of demand-side healthcare culture.Plain language summary: Known information: Healthcare culture encompasses both the facets of supply and demand. Existing research predominantly attends to the supply aspect, delving into the organizational culture within healthcare settings and crafting numerous evaluative instruments, including the Hospital and Safety Culture scales. Conversely, the realm of demand, specifically the healthcare-seeking culture among residents, remains underexplored, with a notable absence of tools to assess the reasonableness of this culture.Contribution of this study: This research quantitatively explores the resident healthcare-seeking culture for the first time, introducing a new theoretical framework to the domain of healthcare culture studies. By developing a scale with robust reliability and validity, this research offers a scientific instrument to evaluate the reasonableness of resident healthcare-seeking culture. Furthermore, this study addresses a previously unexplored void in the investigation of healthcare-seeking culture among residents.Implications of this study: By employing this scale, healthcare providers can gain a deeper insight into the characteristics of resident healthcare-seeking culture among residents across various demographic settings. This understanding enables them to tailor their services more closely to align with the cultural practices surrounding patients’ access to healthcare, thereby enhancing patient satisfaction and collaboration in treatment. Moreover, this scale furnishes valuable data to health policymakers, facilitating the incorporation of patients’ healthcare-seeking cultural traits into the formulation of health policies and the design of more effective and culturally resonant policy initiatives.Keywords: Chinese residents, culture, health care seeking, scale development and validation